1993
DOI: 10.1099/00221287-139-3-585
|View full text |Cite
|
Sign up to set email alerts
|

A Triacyltrehalose Containing 2-Methyl-Branched Unsaturated Fatty Acyl Groups Isolated from Mycobacterium Fortuitum

Abstract: A variety of glycolipids were found in a collection of strains of Mycobacterium fortuitum and two patterns were established by thin-layer chromatography. A compound present in all the strains studied was identified as 2,3,4-triacyltrehalose and its overall structure determined by infrared spectroscopy, nuclear magnetic resonance spectroscopy and gas-liquid chromatography-mass spectrometry. Fatty acyl groups present in this molecule were identified as tetradecanoyl, hexadecenoyl, hexadecanoyl, octadecenoyl, oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…2B, top), indicating that it is 2-methyl C 18 acid. The fragmentation pattern in the mass spectrum indicated that it is an unsaturated acid as previously described (16,26) (Table 2). The fact that the McLafferty ion at m/e 88, characteristic of 2-methyl saturated acids, was not a significant ion indicated that one of the double bonds is at the C-2 position.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…2B, top), indicating that it is 2-methyl C 18 acid. The fragmentation pattern in the mass spectrum indicated that it is an unsaturated acid as previously described (16,26) (Table 2). The fact that the McLafferty ion at m/e 88, characteristic of 2-methyl saturated acids, was not a significant ion indicated that one of the double bonds is at the C-2 position.…”
mentioning
confidence: 83%
“…The resulting monomethyl branched shortchain acids were found in SLs, PATs, and the more polar DATs. Such unsaturated monomethyl branched acids have been reported in the various glycolipids of Mycobacterium fortuitum (1,16,26,30), but their presence in M. tuberculosis has not been previously noted. The use of [1-14 C]propionic acid and careful separation of the methyl esters by argentation chromatography allowed us to detect these minor components.…”
mentioning
confidence: 99%
“…chelonae and M. absccssus) and of a group of strains, the third biovariant complex of M. fortuitum, which is unique in its immunodiffusion pattern and acid production from various carbohydrates (LCvy-Frebault et al, 1983;Pattyn et al, 1974;Silcox et al, 1981). Chemical analyses of the representative strains of the lour species demonstrated the occurrence of species-specific alkali-labile glycolipid in M. fortuitum (Ariza et al, 1994;Gautier et al, 1992;Hamid et al, 1993;Tsang et al, 1984;Sempere et al, 1993) and alkalistable glycolipids in the three other species (L6pez Marin et al, 1991(L6pez Marin et al, , 1992(L6pez Marin et al, , 1994Tsang et al, 1984). The present study was performed to characterize specific glycolipids in six strains that belong to the third biovariant complex of M. fortuitum (mannitol-positive and inositol-positive) and showed that this group of organisms is heterogeneous, in agreement with the data obtained by others by means of genotypic (Kirschner et al, 1992;Springer et al, 1995) and biochemical approaches (Wallace et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of an acetyl group by a fatty acyl substituent may explain the difference in the mobilities of the two glycolipids, as almost identical fatty acyl residues were identified in both studies. Nevertheless, the presence o f a tetraacylated triglucoside may typify some strains of the third biovariant complex, since biochemically well-characterized strains of M. fortuitum, including the type strain, were shown to synthesize alkali-labile glycolipids that consisted of 2,3-acy12trehalose, 2,3,4-acy13trehalose and 2,3,6-acy13trehalose (Ariza et al, 1994;Gautier et al, 1992;Hamid et al, 1993;Sempere et al, 1993). These acyltrehaloses differ from the major alkali-labile glycolipid of the third biovariant complex both in the structure of the carbohydrate moiety and in the location of the acyl substitutents, which suggests that the latter compound is not biosynthetically derived from the former substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation